Information System Analysis of Priority Data Mining Members Cards Using the K-Means Algoritma in Ramayana Panbil : Analisis Data Mining Penentuan Prioritas Penggunaan Member Card Menggunakan Algoritma K-Means Pada Ramayana Panbil - Arnol Holman Tua; Erlin Elisa (International Journal of Technology Vocational Education and Training, 2020)
Data mining is a technology that has been developing for quite a long time. To run a company business, data mining is needed using existing databases. This research uses data mining using clustering methods to get new knowledge that is useful for the company. Members card user transaction data is very useful for company management to increase sales, for example in determining the determination criteria of priority member card users. The algorithm used is K-Means Clustering, which is the process of grouping a number of data or objects into clusters. Testing is done with the Rapid Miner Studio 9.6 application. produce clusters of priority grouping of data using member cards